2009
DOI: 10.1590/s0101-28002009000300004
|View full text |Cite
|
Sign up to set email alerts
|

Sobrevida em hemodiálise crônica: estudo de uma coorte de 1.009 pacientes em 25 anos

Abstract: Pancoast syndrome consists of signs and symptoms resulting from a tumor affecting the pulmonary apex and adjacent structures. The process is typically caused by a neoplasm. The majority of cases of Pancoast syndrome are caused by bronchogenic carcinoma. The most commonly found histologic subtypes are adenocarcinoma and epidermoid carcinoma. There have been very few reports of small cell lung carcinoma in the genesis of Pancoast syndrome. We describe the case of a patient with Pancoast syndrome caused by small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 33 publications
5
11
1
7
Order By: Relevance
“…The overall mortality rate was 24.69%, with an overall survival of 84.71% and 63.32% in one and five years, respectively. This rate is similar to the one reported by Azevedo et al 9 and Silva et al 18 , in which they found 86.2% in a year and 60% in five years; 91% in one year and 64% in five years, respectively. Large studies show 89% survival rates at one year and 57% in five years, respectively, in the countries of the European Dialysis and Transplant Association.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The overall mortality rate was 24.69%, with an overall survival of 84.71% and 63.32% in one and five years, respectively. This rate is similar to the one reported by Azevedo et al 9 and Silva et al 18 , in which they found 86.2% in a year and 60% in five years; 91% in one year and 64% in five years, respectively. Large studies show 89% survival rates at one year and 57% in five years, respectively, in the countries of the European Dialysis and Transplant Association.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have suggested that DM is a predictor of mortality, especially due to cardiovascular causes arising from accelerated aterosclerosis. 20 Similar results have been found in several studies, 18,[21][22][23] although this study did not prove such association. One of the limitations of our study, as well as in the study of Angelo et al, 20 is not to be able to include and evaluate all the variables needed to assess survival in diabetic patients, as the type of DM, smoking, BMI, physical exercise, dyslipidemia.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These rates are comparable to those found by Silva et al 19 , who found survival rates of 91% and 84% in one and two years respectively, in a study carried out in Brazil. Data from dialysis censuses show survival rates of 88.6% in one year and 79.1% in two years in Europe 20 and 77.4% in one year and 63% in two years in the USA 1 .…”
Section: Discussionsupporting
confidence: 90%
“…Silva et al (32) developed a study to assess the spiritual wellbeing of patients with obstructive lung disease (OLD) and found similar means to those in the present study. In their study, the sample presented moderate levels of total SWB, with a mean score of 94.8, and higher scores were observed in the religious well-being subscale (51.50) than existential well-being (43.37).…”
Section: Discussionsupporting
confidence: 82%